1994
DOI: 10.1111/j.1432-1033.1994.tb18598.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, primary structure, crystallization and preliminary crystallographic study of a serine proteinase from Streptomyces fradiae ATCC 14544

Abstract: A proteinase having wide substrate specificity was isolated from Streptomyces fradiae ATCC 14544. This proteinase, which we propose to call SFase-2, was purified from the culture filtrate by S-Sepharose chromatography. The purified enzyme showed an apparent molecular mass of 19 kDa on SDSPAGE. When synthetic peptides were used as substrates, SFase-2 showed broad substrate specificity. It also hydrolyzed keratin, elastin and collagen as proteinaceous substrates. It was completely inhibited by diisopropylfluorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…The amino acid composition of MLP was similar to the composition of alkaline proteases and subtilisins from Bacillus strains, which range in molecular mass from 23,700 to 30,000 Da (18,48) and to the composition of the 19,000-Da alkaline protease from Streptomyces fradiae (26). The greatest number of residues were found as Thr, Ser, Gln/Glu, Gly, Ala, and Val; the seven reported Bacillus enzymes, however, in contrast to MLP, contained no cysteine residues.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The amino acid composition of MLP was similar to the composition of alkaline proteases and subtilisins from Bacillus strains, which range in molecular mass from 23,700 to 30,000 Da (18,48) and to the composition of the 19,000-Da alkaline protease from Streptomyces fradiae (26). The greatest number of residues were found as Thr, Ser, Gln/Glu, Gly, Ala, and Val; the seven reported Bacillus enzymes, however, in contrast to MLP, contained no cysteine residues.…”
Section: Discussionmentioning
confidence: 93%
“…luteus protease was significantly inhibited by the serine enzyme inhibitor PMSF and the chymotrypsin inhibitor chymostatin. These findings indicate that MLP is a member of the chymotrypsin superfamily of the serine proteases, such as those produced by certain Streptomyces and Bacillus species (18,20,26).…”
Section: Discussionmentioning
confidence: 98%
“…Brayer et al reported that the S2 pocket in S. griseus proteinase A is probably a necessary prerequisite for proper substrate orientation as a result of reduced specific binding in the S1 site [29). A kinetic study of SFase-2 showed that substitution of the alanine residue by proline in the P2 position increased the k,J K,, value tenfold, to give a value similar to that of proteinases A and B from S. griseus [19]. It would be interesting to Residue numbers are given for SFase-2 (Fig.…”
Section: Crystal Structure Of Sfase-2mentioning
confidence: 96%
“…The molecular mass of NAPase, estimated as 20 kDa (Fig. 2), was close to other proteases of actinomycetes origin such as Protease A (18 kDa) and B (19 kDa) from Streptomyces griseus, 11) SFase-2 (19 kDa) from Streptomyces fradiae, 12) and protease I(21 kDa) from Nocardiopsis dassonvillei.…”
mentioning
confidence: 99%